PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN SOFT SKILL “PEMBUATAN ABON PEPAYA” DALAM UPAYA PENINGKATAN PENDAPATAN KELUARGA DI LINGKUNGAN SONGGELA KELURAHAN ULE KOTA BIMA - Huda, Nurul; Jaenab; Ernawati, Sri; Pratiwi, Aliah; Rahmatia, Nafisah Nurul (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This Community Service aims to increase the knowledge and skills of the IRT women group through the transformation of processing technology, marketing, marketing and business management using Papaya as a processed product of Papaya Shredded. The problem is the low knowledge and skills of IRT in processing papaya so that it becomes a product that has economic value. The target of this program is the formation of a business unit that develops food products from papaya. Specifically, this program aims to train Housewives (IRT) to produce Papaya Shredded. The training is provided starting from how to process, packaging, marketing to the method that will be applied to achieve the goal or target is the method of demonstration, training / counseling. This activity involved members of the Real Work Lecture students who were accompanied by a lecturer accompanying the management study program with the participants being housewives (IRT) in Ule Village and the community in Ule Village, Bima City. The results achieved in this activity are that the Housewife Group (IRT) has understood and has the skills and entrepreneurship, knows how to manage a more structured business, the existence of shredded products and understands how to market products with packaging innovation and the use of technology. The results of the evaluation that have been carried out can be seen that the knowledge of participants regarding tuna bone processing has increased and opened the minds of participants to take advantage of existing opportunities to increase income. Approximately 80 percent of participants actively responded positively to the skills and knowledge conveyed by the Service Team.